ANALISIS PENGARUH KEBUDAYAAN, SOSIAL, KEPRIBADIAN DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN SHAR’E (Survei pada nasabah Bank Muamalat Indonesia Cabang Purwokerto - Darmawati, Dwita; Subekti, Bambang; Setyawati, Sri Murni; Sumarsono, Sumarsono (Performance, 2007)
The aims of research are first to find out and analyze the effect of culture, social, personality and psychology on buying decision of shar’e product. The second it aims to find out and analyze which of the four factors has the greatest effect on buying decision of Shar’e product. Sample of this research consist of 100 customer of Bank Muamalat Indonesia Purwokerto Branch. Path analysis is the instrument used to find out the direct or indirect effect of the four variables on customers buying decision. Based on the result of analysis using F-test and t-test shows that that only personality variable (X3) and psycology variable (X4) have significant effect on Shar’e product buying decision, as they are greater than t-table Next based on the result of calculation, it has got that Path coeficient of personality variable greater than Path coefficient of psychology variable. It shows that effect of personality variable is greater than psychology variable.